Incidence and prevalence of postpartum depression in a rural community of India - Shrestha, N; Hazrah, P; Sagar, R (Journal of Chitwan Medical College, 2015)
Postpartum depression (PPD) is defined as presence of depressive symptoms in the postpartum period. A seemingly innocuous disorder, if untreated can lead to foeticide or maternal suicide. Unfortunately there are very few studies which have looked into the burden of the disease. The prevalence and incidence of postpartum depression vary across culture, region and communities, with very few studies having addressed the issue, thereby making it difficult to estimate the actual burden of the disease. The present study was undertaken to estimate the incidence and prevalence of postpartum depression in a rural community of India. A cohort of 200 pregnant women were interviewed in the third trimester of pregnancy and subsequently at 6 weeks postpartum to screen for presence and severity of depressive symptoms using BDI, ICD10 and EPDS scores. A cutoff score > 13 was considered as positive for depression in EPDS. The prevalence of PPD was 12% and incidence of PPD 4.4%.